Calculation of the high-level waste maximum activity of the Chornobyl NPP operating origin during storage in KTZV-0.2 containers - V. V. Derengovskyi; S. V. Kupriianchuk; D. O. Khomenko; D. V. Fedorchenko (Ядерна фізика та енергетика)
This paper decrypts the conceptual design of the cask’s control radiation system of high-level waste (HLW). This system is intended for the solid radioactive waste processing plant at Chornobyl NPP and is capable of forming a passport for a batch of HLW, based on the measured surface dose rate (DR) for KTZV-0.2 protective container. DR for primary packaging and KTZV-02 container were calculated using Monte Carlo simulation code MCNP 6.2. The typical material compositions of the Chornobyl NPP radioactive waste, contaminated by 137Cs and 60Co, were considered, and the corresponding surface DR was calculated. The simulation results were used for the development of the HLW cask load criterion for the radiation loading control system. The paper shows that HLW load criterion could be safely increased from 80 to 280 mSv/h.